2021
DOI: 10.1002/smll.202100372
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of an Au25‐Cys‐Mo Electrocatalyst for Efficient Nitrogen Reduction to Ammonia under Ambient Conditions

Abstract: Ammonia (NH 3 ) is an essential nitrogen feedstock for fertilizer and efficient energy carrier. [1,2] The traditional process for synthesizing NH 3 is mostly produced via the Haber-Bosch process. [3] Up to now, the well-established Haber-Bosch process Electrocatalysts for efficient production of ammonia from nitrogen reduction reaction (NRR) under ambient conditions are attracted growing interest in recent years, which demonstrate a great potential to replace the Haber-Bosch method which suffers the problems o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…[10][11][12][13][14][15][16] Nowadays, ammonia is mainly produced by the energy-intensive and highly polluting Haber-Bosch process. [17][18][19][20] Alternatively, electrocatalytic nitrate reduction to ammonia, due to its high efficiency and environmental characteristics, raises a storm of discussions and has a great impact on media and public imaginations. [21][22][23][24] The past decade has witnessed signicant progress in the study of electrocatalytic nitrate reduction to ammonia.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16] Nowadays, ammonia is mainly produced by the energy-intensive and highly polluting Haber-Bosch process. [17][18][19][20] Alternatively, electrocatalytic nitrate reduction to ammonia, due to its high efficiency and environmental characteristics, raises a storm of discussions and has a great impact on media and public imaginations. [21][22][23][24] The past decade has witnessed signicant progress in the study of electrocatalytic nitrate reduction to ammonia.…”
Section: Introductionmentioning
confidence: 99%
“…+ in the acidic solution, contrasting to the triplet pattern with a coupling constant of 52 Hz for 14 NH 4 + . [66,67] This result unambiguously revealed that the NH 3 indeed originates from N 2 fixation. To further confirm the reliability, the quantitative analysis of isotope 1 H NMR spectra were carried out.…”
Section: Nhmentioning
confidence: 69%
“…The application of Au NCs as electrocatalysts to explore the transformation of dinitrogen (N 2 ) to ammonia (NH 3 ) through the electrocatalytic process is another interesting research topic. However, so far very few reports have demonstrated the NRR using mono- or bimetallic Au NCs. Nevertheless, in most cases, the yields of NH 3 and FEs were much less due to the competing HER. Therefore, the key strategies to improve the yield of NH 3 would be constraining the competing HER and introducing more active sites by modulating the electronic structure of active sites.…”
Section: Discussionmentioning
confidence: 99%